Phytoremediation Effectiveness of Salvinia molesta and Hydrilla verticilla-ta L. in Treating Batik Industrial Wastewater - Natasya Dwi Anjani anjani; Tarzan Purnomo; Fida Rachmadiarti; Sunu Kuntjoro (BIOVALENTIA: Biological Research Journal, 2026)
Batik industrial wastewater contains organic pollutants and suspended solids that may degrade water quality if discharged without treatment. Phytoremediation using aquatic plants offers an environmentally friendly alternative for wastewater management. This study aimed to evaluate the effects of plant type and detention time on the phytoremediation efficiency of batik wastewater using Salvinia molesta, Hydrilla verticillata, and their combination. The experiment was conducted using a Randomized Block Design with detention times of 0, 7, and 14 days. Water quality parameters, chlorophyll content, and plant biomass were analyzed using two-way Analysis of Variance (ANOVA) followed by Duncan’s Multiple Range Test (DMRT) at a significance level of p < 0.05. The results demonstrated that both plant type and detention time significantly improved wastewater quality (p < 0.05). The combined plant treatment at 14 days produced the most effective remediation, indicated by reduced BOD, TSS, and turbidity and improved pH conditions within quality standards. Longer detention time enhanced phytoremediation performance and supported plant growth under wastewater conditions. These findings highlight the ecological synergy between floating and submerged aquatic plants as a promising nature-based solution for sustainable batik wastewater treatment.